From Lake to Ocean: Disentangling past and present depositional processes and environmental conditions of sub-Antarctic South Georgia using molecular and isotopic tools - Jivcov, Sandra (2019)
The sub-Antarctic is a key region for the understanding of the coupling of Northern and Southern Hemispheres’ reactions to climate change. Until now, only few marine sedimentary records from this region were investigated because they are often lacking in eligible mate- rial for radiocarbon dating. Here, this topical problem is addressed by compound-specific radiocarbon analysis (CSRA) of biomarkers, derived from sedimentary records of South Georgia. Intrinsic characteristics of different biomarkers as well as depositional processes were investigated, in order to identify suitable compounds for the development of confident sediment chronologies. Environmental changes in the study area were traced on the basis of comprehensive multi-proxy analyses of marine and lacustrine sedimentary records. Radiocarbon ages of n-fatty acids, n-alkanes, n-alcohols, total organic carbon (TOC) and macrofossils of a coastal marine sediment core (Co1305) of Little Jason Lagoon and a lacus- trine sediment core (Co1308) of Allen Lake A were measured, in order to identify sources of the organic matter and to asses timescales of sediment transport. Similar temporal offsets of c. 1,900 to 2,600 years between production and deposition of co-occurring plant macrofos- sils and high molecular weight (HMW) n-fatty acids and n-alkanes point to common origins and transport pathways of these different sample types. Preservation and retention of the organic matter on land seems to be favored by climatic conditions. Sedimentary bedrock is another source of land-derived organic carbon (OC) in the study area. Petrogenic OC is commonly free of 14C and therefore influences radiocarbon ages of bulk sediments considerably. In order to quantify the contributions of OC from petro- genic, terrigenous (plants and soils) and marine sources to the surface sediments of different aquatic environments (a lake, a marine inlet, two fjords and an off-shore site), three end- member mass balance calculations were successfully applied. A clear spatial trend in the ...